Sagittal Plane Correction in Fixed Cervical Deformity - Hazem Alkosha (Egyptian Spine Association, 2016)
Background Data: Fixed cervical deformities are devastating pathological entities that interfere with normal daily activities and may progress to leave patients bedbound. Purpose: To present early experience and outcome of managing fixed cervical deformities, and to explore the safety and efficacy of the methods used. Study Design: A retrospective clinical case series that tracks subjects with fixed cervical deformities as regard presentation, treatment and outcome. Patients and Methods: Patient sample included those presented with kyphotic segmental deformities causing regional angular and translational deformities with presenting clinical picture related to the deformity. The patients were corrected by either anterior-only or combined approached, with assessment of outcome using radiological sagittal plane profile, neurological improvement (Nurick classification) and overall work capacity (Odom’s criteria). Results: Eleven patients (78.6%) underwent anterior-only, while 3 patients underwent combined approaches in posterior-anterior-posterior fashion. Perioperative complications were minor and managed conservatively. The mean correction in segmental kyphosis was 27.3±6.7 degrees, that of regional kyphosis was 29±12 degrees, while mean correction in cervical SVA was 22±12 mm. Lordotic curves were achieved in 68.5% of patients (the overall mean of postoperative C2-C7 angle=9±6.4o). The mean improvement in Nurick grades was 1.5 and the good (Odom grade 2) to excellent (Odom grade 3) outcome was reported by 10 (71%) of our patients. Conclusion: Sagittal plane-based correction of cervical fixed kyphosis is a safe and effective strategy that spinal surgeons should bear in mind in addition to the usual neural decompression target.Angular and translational should be both used in assessment as they may be no closely correlated. (2016ESJ114)